Co-pyrolysis behavior of sewage sludge and rice husk by TG-MS and residue analysis. (20th March 2020) - Wang, Teng; Chen, Yuchi; Li, Jinping; Xue, Yongjie; Liu, Jingxin; Mei, Meng; Hou, Haobo; Chen, Si
Abstract: Co-pyrolysis sewage sludge (SS) and rice husk (RH) is a promising method for reusing the waste. In this study, thermogravimetry and mass spectrometry (TG-MS) were used to investigate the thermal degradation behavior and the evolution of gaseous species during co-pyrolysis. The interactions of SS and RH on gas and biochar products were explored. The results reveal that the introduction of RH can improve the pyrolysis reactivity and CO2 production of SS, but reduce the cumulation of H2, CH4 and C2 H2 . The interaction inhabited the main gases generation, while promoted carbonization and aromatization of the corresponding biochar, especially under 30%RH addition. The addition of RH can lead to pore development and a sharp improvement in specific surface area under high dose. Overall, co-pyrolysis of RH and SS captures more gaseous hydrocarbons and provides biochar with remarkable adsorption potential. Highlights: Effect of RH additive on pyrolysis behavior of SS. In-situ monitoring of the evolved gas products of SS-RH mixture by TG-MS. Occurrence of interaction affect on multiphase products during co-pyrolysis.